1999
DOI: 10.1016/s0168-6496(99)00002-1
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium addition inhibits 13C-methane incorporation into methanotroph membrane lipids in a freshwater sediment

Abstract: To investigate the effect of ammonium addition on the species composition and activity of freshwater methane oxidizing bacteria, intact sediment cores were labeled with IQ CH R and incubated under ambient and elevated ammonium concentrations. After 7 days, methanotroph activity was assessed by quantifying the isotopic composition of the carbon in membrane lipids. The 16-carbon rather than the 18-carbon methanotroph-specific biomarkers showed a clear enrichment in IQ C, suggesting the importance of group I meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…In the freshly harvested sediment before [methyl‐ 13 C]toluene incubation, this compound was significantly depleted (−40.3‰) relative to averaged values of the total of PLFA (−28.9‰), reflecting CH 4 assimilation because biogenic CH 4 has a depleted carbon isotopic signal (−65 to −50‰). This depleted isotopic signal supported previous suggestions that 16:1ω5 is characteristic for group I methanotrophs [40]. However, it has been shown that 16:1ω5 is also commonly found in other Gram‐negative bacteria, including strain PRTOL1 (Table 3) and other genera of sulfate‐reducing bacteria [14,16].…”
Section: Discussionsupporting
confidence: 88%
“…In the freshly harvested sediment before [methyl‐ 13 C]toluene incubation, this compound was significantly depleted (−40.3‰) relative to averaged values of the total of PLFA (−28.9‰), reflecting CH 4 assimilation because biogenic CH 4 has a depleted carbon isotopic signal (−65 to −50‰). This depleted isotopic signal supported previous suggestions that 16:1ω5 is characteristic for group I methanotrophs [40]. However, it has been shown that 16:1ω5 is also commonly found in other Gram‐negative bacteria, including strain PRTOL1 (Table 3) and other genera of sulfate‐reducing bacteria [14,16].…”
Section: Discussionsupporting
confidence: 88%
“…Groups of biomarker PLFA: gram‐positive (G+ve) bacteria (branched‐chained iso/anteiso FA), gram‐negative (G−ve) (monounsaturated and cyclic FA), actinobacteria (10Me‐branched FA) and fungi (18:2 ω 6,9) and non‐specific PLFA [16:0,18:0]. % 13 C incorporation calculated using I = ( F e − F c )[PLFA] c (after Nold et al , 1999). Error bars represent standard deviation ( n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…δ 13 C values obtained for methylated compounds were corrected for the addition of derivative C using the mass balance equation: where n = number of C atoms, c = δ 13 C value of the underivatized compound, d = δ 13 C value of the derivatizing agent (BF 3 MeOH; bulk δ 13 C value −34.1‰, determined by continuous flow‐IRMS) and cd = δ 13 C value of the derivatized compound. The fractional abundance ( F ) of 13 C in the control ( F c ) and enriched ( F e ) PLFA was used to calculate the concentration of 13 C incorporated into PLFA from the total PLFA concentration, using the equation I = (Fe − Fc)[PLFA]c (after Nold et al , 1999). The fractional abundance expresses the concentration of 13 C as a proportion of the total concentration of carbon in the PLFA using the equation F = [ 13 C/ ( 13 C + 12 C )].…”
Section: Methodsmentioning
confidence: 99%
“…The fractional abundance expresses the concentration of 13 C as a proportion of the total concentration of C in the PLFA using the equation described by Nold, Boschker, Pel, and Laanbroek () normalF=[]13normalC/()13normalC+12normalC …”
Section: Methodsmentioning
confidence: 99%